Ett kortare liv än andra? Dödsrisker, funktionsnedsättningar och attityder i 1800-talets samhälle - Vikström, Lotta; Haage, Helena (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2015)
This study follows disabled individuals over their lifespan to examine their mortality risks in 19thcentury society, in comparison to non-disabled people. The aim is to detect whether people, due to their disability, had a higher probability of meeting a premature death. We use Sweden’s 19th-century parish registers to identify people the ministers defined as disabled, and employ theories on deviance and gender to grasp the statistical mortality findings. Disability significantly jeopardized the survival of individuals and particularly of men, probably because impairment limited their chances to match the breadwinner ideals associated with the male gender.